Resistance Test of Potential Mercury-Reducing Bacteria Using Agar Plate Method - Amandita, Fitri Yola; Efadeswarni, Efadeswarni; Aini, Nabillah; Fatma, Lania Yuchanitz (Graduate School, Universitas Brawijaya, 2024)
The restoration of mercury-contaminated sites is a global concern, and countless studies have been conducted to formulate the best remediation practice. Mercury pollution in Indonesia has been a national issue. Thus, the government has enforced the reduction and elimination of this toxic and persistent chemical element and its compounds since 2019. As claimed to be the most environmentally friendly and cost-efficient technique, bioremediation using indigenous bacteria offers excellent potential to be implemented in developing countries such as Indonesia. This study is a preliminary part of four-year research at formulating a bioremediation technique to restore mercury-contaminated soils, especially in agricultural areas. In this investigation, fifteen indigenous bacterial isolates were tested for their resistance to mercury using two different techniques: the agar plate method, namely the disk-diffusion technique, and a modified version of the cup-plate technique. Inhibitory zone diameter (IZD) was measured and compared using Bland-Altman analysis between two techniques with supplementation of HgCl2 2-100 ppm range to the Mueller-Hinton agar media. The disk-diffusion technique appeared to give inconsistent measurements of IZD along the increase of HgCl2 concentration, in which the highest IZD mean was obtained from samples with 8 and 10 ppm HgCl2. Meanwhile, the cup-plate technique shows a lower average of IZD compared to the disk-diffusion technique. This report provides insights on the resistance of potential bacteria for mercury bioremediation. Further study should consider the accuracy of the agar plate method to test the bacterial resistance to any particular compound. Keywords: bioremediation, cup-plate, disk-diffusion, inhibitory zone diameter, method accuracy.